Experimental study of a thermosiphonic hybrid PV/T solar system - Souliotis, Manolis; Tripanagnostopoulos, Yiannis; Kalogirou, Soteris A.; Florides, Georgios A.; Ekhrawat, Monir; Tsipas, Dimitris (My University, 2008)
Flat Plate Thermosiphonic Units (FPTU) and Photovoltaic devices are well known solar systems that provide heat and electricity, respectively. The hybrid Photovoltaic/Thermal (PV/T) solar systems can simultaneously provide electricity and heat, achieving a higher conversion rate of the absorbed solar radiation than standard PV modules. When properly designed PV/T systems can extract heat from PV modules, heating water or air, aiming to reduce the operating temperature of PV modules and to keep the electrical efficiency at a sufficient level. In this paper we present design considerations and experimental results of a thermosiphonic hybrid PV/T solar system that is investigated at the University of Patras. The system is analyzed with respect to the design and the electrical and thermal energy output for a pc-Si PV module type under the climatic conditions of Patras.
Keywords: Photovoltaics; Thermosiphonic Solar Collectors; Hybrid PV/T